Seven new species of the genus Physotarsus Townes 1966 (Hymenoptera, Ichneumonidae) from South America - Reshchikov, Alexey; Sääksjärvi, Ilari Eerikki (Zootaxa, 2015)
Seven new species of the genus Physotarsus Townes are described and illustrated: P. iquitos Reshchikov and Sääksjärvi sp. n., P. mishanensis Reshchikov and Sääksjärvi sp. n., P. orellanensis Reshchikov and Sääksjärvi sp. n., P. polleti Reshchikov and Sääksjärvi sp. n., P. saltilloensis Reshchikov sp. n., P. tampobata Reshchikov and Sääksjärvi sp. n., and P. tunchi Reshchikov sp. n. The male of P. oculatus Zhaurova, 2009 is described for the first time. An illustrated key for Neotropical species is provided.